Control of parallel inverters in microgrid - Liu, Jiazhe (2019)
With the development of renewable energy sources, the microgrid is widely implemented because of its flexibility and high-efficiency. It makes the most use of distributed generators and energy storage systems, which can supply the local load with minimum energy loss. However, there are always two concerns in the microgrid. The first one is power sharing. Generally, power sharing is designed to be proportional to the generator’s capacity to reach the highest efficiency. Droop control, which is well-known for its noncommunication control strategy, can achieve proportional active and reactive power sharing among parallel power converter systems. However, its feasibility can be seriously influenced by some additional factors, such as line impedance mismatch, different types of line impedance and sensor error. Thus, in this report, the power sharing of the droop control with various disturbances are comprehensively discussed and the corresponding method to mitigate the power sharing error is proposed. The other concern is power quality. The droop control is only responsible for the power sharing in the fundamental domain but cannot control the currents in the harmonic domain. However, in the microgrid, the widely implemented nonlinear load can inject the harmonic currents in the microgrid and cause the voltage distortion at the point of common coupling (PCC). Besides, switching deadtime of the converter is another harmonic source, which can generate large harmonic circulating currents when the line impedance is small. To simultaneously suppress the circulating current harmonics and mitigate the PCC voltage harmonics, a novel control strategy is proposed based on virtual harmonic impedance controls. The feasibility of the proposed control strategies is verified through the Matlab/Simulink simulations or scale-down experiments.